2020
DOI: 10.3389/fsufs.2020.00020
|View full text |Cite
|
Sign up to set email alerts
|

Forest Conservation: A Potential Nutrition-Sensitive Intervention in Low- and Middle-Income Countries

Abstract: Childhood undernutrition yearly kills 3.1 million children worldwide. For those who survive early life undernutrition, it can cause motor and cognitive development problems that translate into poor educational performance and limited work productivity later in life. It has been suggested that nutrition-specific interventions (e.g., micronutrient supplementation) that directly address the immediate determinants of undernutrition (e.g., nutrient intake) need to be complemented by nutrition-sensitive intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The authors acknowledge this is probably due to self‐selection, with more highly educated households seeking advice from extension services. This parallels findings in other studies that evaluate agriculture and nutrition projects, where education is shown to enhance the efficacy of various nutrition‐sensitive interventions (Rasolofoson et al, 2020). With tree‐based farming, education and wealth are key assets that can motivate farmers to make the initial long‐term investment and the ability to manage the time‐lag between planting and harvest.…”
Section: Resultssupporting
confidence: 83%
“…The authors acknowledge this is probably due to self‐selection, with more highly educated households seeking advice from extension services. This parallels findings in other studies that evaluate agriculture and nutrition projects, where education is shown to enhance the efficacy of various nutrition‐sensitive interventions (Rasolofoson et al, 2020). With tree‐based farming, education and wealth are key assets that can motivate farmers to make the initial long‐term investment and the ability to manage the time‐lag between planting and harvest.…”
Section: Resultssupporting
confidence: 83%
“…However, though buffer zones and "zones of utilization" within and around PAs have become increasingly common, many fortress-style PAs still forbid the collection of wild plants from within their boundaries. Despite evidence that reduced access to wild foods can negatively affect FSN, specifically micronutrient consumption (Johnson et al, 2013;Powell et al, 2015;Galway et al, 2018;Rasolofoson et al, 2020), the impact of PAs on food security, and human wellbeing in general, remains under-examined in the literature (Pullin et al, 2013;Jouzi et al, 2020). Of the studies focusing on wild food access in these spaces, most has focused on wildlife (e.g., Golden et al, 2011;Mavah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The association between forest cover/vegetation and childhood stunting has previously been observed in a few other studies that use different vegetation proxies (most often, the NDVI). Using data from 25 low- and middle-income countries, Rasolofoson et al [ 38 ] have demonstrated that exposure to forests significantly reduces child stunting (by around 7%). Sununtnasuk [ 39 ] also showed the NDVI statistically reducing the probability of stunting in Nepal.…”
Section: Discussionmentioning
confidence: 99%